1941
DOI: 10.1017/s0022172400012523
|View full text |Cite
|
Sign up to set email alerts
|

Observations on ‘hospital infection’ in a plastic surgery ward

Abstract: Over a period of 6 months, wounds and throats in a plastic surgery ward were swabbed. Haemolytic streptococci obtained from them were typed by the late Dr F. Griffith and his staff at the M.E.C. Streptococcal Research Laboratory. 65% or more of the wounds in the ward were found to be infected with Streptococcus pyogenes, but relatively few suffered severe damage as a result of their infection.About a quarter of the cases admitted to the ward acquired streptococcal wound infections while in the ward. Two wound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1944
1944
1954
1954

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Hospital blankets are undoubtedly an important source of cross-infection, and much stress has been laid on their contribution to dust-borne bacterial disease (Deicher, 1927 ;Thomas, 1941 ;Spooner, 1941 ;Van den Ende, Edward & Lush, 1941 ;Garrod, 1944; Wright, Cruickshank t Gunn, 1944;Puck et al, 1946;Loosli et al, 1950). We have shown that soap-and-water laundering does nothing towards sterilizing blankets and, in fact, only redistributes the bacteria among them, thus indicating a route of infection from patient to patient and even from ward to ward.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital blankets are undoubtedly an important source of cross-infection, and much stress has been laid on their contribution to dust-borne bacterial disease (Deicher, 1927 ;Thomas, 1941 ;Spooner, 1941 ;Van den Ende, Edward & Lush, 1941 ;Garrod, 1944; Wright, Cruickshank t Gunn, 1944;Puck et al, 1946;Loosli et al, 1950). We have shown that soap-and-water laundering does nothing towards sterilizing blankets and, in fact, only redistributes the bacteria among them, thus indicating a route of infection from patient to patient and even from ward to ward.…”
Section: Discussionmentioning
confidence: 99%
“…Excised tissue wm well rubbed up in the broth in the collecting bottle with a sterile glass rod and the broth then transferred to the same culture media as were used for the swab samples. Staphylococci and streptococci were isolated from cultures containing Proteus vulgaris by the use of the Butcher plate (Spooner, 1941a) or latterly on blood agar plates containing 6 per cent. of agar instead of the usual 2 per cent.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…The occurrence of wound to wound infection has been attested by several recent reports (Miles et al, 1940;Spooner, 1941;McKissock, et al 1941) and McKissock et al were able to show that it could be controlled by the introduction of a dressing technique designed to minimize the transference of pathogenic organisms from one wound to another. We have been able to confirm these observations (Williams, Clayton-Cooper, Howat and Miles, unpublished).…”
Section: Introductionmentioning
confidence: 99%